Aporia of Participatory Planning: Framing Local Action in the Entrepreneurial City - Ryan Love (Footprint)
This essay examines the hegemonic-discursive barriers facing local action in cities today, first, by revisiting the New Left/Frankfurt School critique of modern institutions, which not incidentally proved a key inspirational source for the original grassroots movements of the 1960s and 1970s.